Microfluidic Co‐Culture Platform to Recapitulate the Maternal–Placental–Embryonic Axis. Issue 8 (19th June 2021) - Boos, Julia A.; Misun, Patrick M.; Brunoldi, Giulia; Furer, Lea A.; Aengenheister, Leonie; Modena, Mario; Rousset, Nassim; Buerki‐Thurnherr, Tina; Hierlemann, Andreas
Abstract: Safety assessment of the effects of developmental toxicants on pregnant women is challenging, and systemic effects in embryo–maternal interactions are largely unknown. However, most developmental toxicity studies rely on animal trials, while in vitro platforms that recapitulate the maternal–placental–embryonic axis are missing. Here, the development of a dedicated microfluidic device for co‐cultivation of a placental barrier and 3D embryoid bodies to enable systemic toxicity testing at the embryo–maternal interface is reported. The microfluidic platform features simple handling and recuperation of both tissue models, which facilitates post‐hoc in‐depth analysis at the tissue and single‐cell level. Gravity‐driven flow enables inter‐tissue communication through the liquid phase as well as simple and robust operation and renders the platform parallelizable. As a proof of concept and to demonstrate platform use for systemic embryotoxicity testing in vitro, maternal exposure to plastic microparticles is emulated, and microparticle effects on the embryo–placental co‐culture are investigated. Abstract : A microfluidic platform to recapitulate the maternal–placental–embryonic axis is presented. A microphysiological model of the placental barrier is integrated into a hanging‐drop network and co‐cultured with embryoid bodies in a single, gravity‐driven fluidic network. Maternal exposure to plastic microparticles is emulated to demonstrate the potential of the platform to study systemic toxicity effects at the embryo–maternal interface.